Influence of environmental factors on fish assemblages in streams of the Elbe and Oder basins - Luboš Kůra (Frontiers in Marine Science, 2015)
The effects of environmental parameters on changes in the structure of fish assemblages were studied in the Elbe and the Odra basin. Research was done at 819 sites surveyed in the field during the period 1993-2007. The impact of 46 factors derived from the maps through a GIS was tested as well as the impact of 10 factors recognized in the field. To evaluate the influence of these factors the indirect (DCA) and direct (CCA) multivariate cluster analysis were used. Analyses were performed with data on presence-absence and relative abundance of each species. DCA well reflects changes in assemblages in the longitudinal profile of streams. CCA refers to a significant influence of regional and temporal variability and influence of individual factors. The fish assemblages are best characterized by distance from the source location, stream slope, altitude of locality, representation of arable land in the basin, number of ponds in the sub-basin above the locality, type of waters (salmonid or cyprinid), and water temperature (the only of the parameters of the field). The analyzed factors better reflect the variability in fish assemblages of the Odra than of Elbe river basin. The analysis showed good practical efficiency of processing information from a large sample of data from ichthyological surveys. The tools of GIS and the use of statistical methods make possible to characterize basic ecological requirements of most species and specify conditions determining specific composition of fish assemblages.